Educational policy and educators’ academic integrity - Zejno, Bukuri (IIUM Press, 2019)
Abstract: Academic integrity is an issue that has received tremendous attention and continues to be an intense area of research involving all levels of scholarship, mainly due to the impact of its opposite concept and academic dishonesty on the reputation of an institution or the members of that institution, be it students or academicians. However, while most researches deal with plagiarism by students and other unethical practices, not much is being said about this phenomenon among staff and academics. In order to find effective solutions to a problem, it is essential to dig into the roots of that problem and investigate what are the potential causes of it. Therefore, building on previous research, this paper uses an analytical approach to look at a number of aspects within the educational system that are found to stimulate plagiarism and academic dishonesty among the educators and academic professionals, such as lack of awareness, pressurizing circumstances, deficiency in the application of concepts of justice and equality, as well as non-compliance with the underlying worldview upheld by the educational institution. This paper attempts to give suggestions about the measurements that need to be taken into consideration by the educational system and policy makers, in the quest of providing longterm solutions that can lead to a culture of academic integrity, particularly for Islamic educational institutions.